Suicide Ideation and Attempts among First Nations Peoples Living On-Reserve in Canada: The Intergenerational and Cumulative Effects of Indian Residential Schools - McQuaid, Robyn Jane (Can J Psychiatry, 2017)
OBJECTIVE: Suicide rates among Indigenous peoples in Canada are at least twice that of their non-Indigenous counterparts. Although contemporary stressors contribute to this increased risk, historical experiences such as the Indian Residential School (IRS) system may also have continuing links with the risk for suicidal thoughts and behaviors. The current investigation examined the intergenerational and cumulative links between familial IRS attendance in relation to lifetime suicide ideation and attempts among First Nations adults living on-reserve. METHOD: Data from the 2008-2010 First Nations Regional Health Survey were analyzed, and participants comprised a representative sample of First Nations adults older than 18 years (weighted N = 127,338; IRS attendees were excluded). Of those who knew their familial IRS history, 38.0% had no history of attendance, 19.3% had a grandparent who attended, 16.2% had a parent who attended, and 26.5% had a parent and grandparent who attended. RESULTS: Exposure of one previous familial generation to the IRS experience was associated with increased risk for lifetime suicide ideation (odds ratio [OR], 1.46; 95% confidence interval [CI], 1.16 to 1.84; P = 0.001) and attempts (OR, 1.44; 95% CI, 1.07 to 1.94; P < 0.016) compared with those with no IRS history. Having 2 generations of IRS familial history was associated with greater odds of reporting a suicide attempt compared with having one generation (OR, 1.35; 95% CI, 1.05 to 1.75; P = 0.022), which was reduced when current levels of distress and ideation were accounted for. CONCLUSION: Findings support the existence of linkages between intergenerational exposure to IRS and risk for suicidal ideation and attempts and for a potential cumulative risk in relation to suicide attempts across generations.